The Effectiveness of Leadership and Employee Compensation on Improving Employee Performance in the Planning Bureau of the Secretariat General of the Ministry of Agriculture - Assa, Adrie F. (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to analyze the relationship between leadership and employee compensation within the Planning Bureau of the Secretariat General of the Ministry of Agriculture using a qualitative, descriptive approach. The researcher acted as the main research instrument, conducting interviews, collecting, and analyzing data to provide insights. The study identified that the bureau employs a participatory leadership style, as evidenced by interview findings. Employee compensation includes both direct and indirect forms, such as fair personnel management and a supportive work environment. The results indicate that effective leadership and fair compensation practices encourage employee responsibility and contribute to achieving organizational goals, leading to performance that meets management's expectations.